Speed Control of Three Phase Induction Motor Using Scalar Method and PID Controller - Nasser, Aram; Szemes, Péter Tamás (Recent Innovations in Mechatronics, 2018)
This paper presents the speed control of a three-phase induction motor using the scalar control method with PID controller. The system maintains a constant volt to frequency ratio for any change in the load. We also used vector control method and bond graph to describe the motor model, as well as its behavior. Finally, we simulated the system using Labview, where the good results of using the scalar control technique are shown.